63 Adult Outcomes in Achievement and Social Integration. (October 2012) - Anderson, P
Abstract : The lecture will provide a wide overview of studies on achievements as indicated by academic and occupational outcome and independent living of those born preterm. The lecture will further explore how well preterm children are integrated into society, participate in peer activities, have formed partner relationships and are reproductively active. How do they view their quality of life? Most of these studies have focussed on very preterm or very low birth weight infants but where available, information on moderate to late preterm adults will also be addressed.